2021
DOI: 10.1111/obr.13337
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and mortality among endometrial cancer survivors: A systematic review and meta‐analysis

Abstract: Summary Excess body fat is a major risk factor for endometrial cancer incidence, but its impact on recurrence and survival remains unclear. The aim of this systematic review and meta‐analysis was to assess the association between excess body fat with recurrence, cancer‐specific, and all‐cause mortality among endometrial cancer survivors. We searched MEDLINE and EMBASE databases up to July 2021. Risk of bias was assessed with the Ottawa Newcastle Scale. Random effects models estimated pooled hazard ratios for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 77 publications
2
20
1
1
Order By: Relevance
“…In particular, two large population-based studies have reported that increased BMI is strongly associated with cancer-specific mortality from endometrial cancer [ 35 , 36 ]. Notably, and consistently with our results, a recent meta-analysis showed that when assessing the prognostic role of obesity according to endometrial cancer subtypes, the association between higher BMI and recurrence was significant among type I cases alone [ 37 ]. We did not find any correlation between BMI and tumor grading; this could surely have been influenced by the fact that we assessed high-grade endometrioid tumors together with type II non-endometrioid tumors, since they have been shown to share similar prognosis [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…In particular, two large population-based studies have reported that increased BMI is strongly associated with cancer-specific mortality from endometrial cancer [ 35 , 36 ]. Notably, and consistently with our results, a recent meta-analysis showed that when assessing the prognostic role of obesity according to endometrial cancer subtypes, the association between higher BMI and recurrence was significant among type I cases alone [ 37 ]. We did not find any correlation between BMI and tumor grading; this could surely have been influenced by the fact that we assessed high-grade endometrioid tumors together with type II non-endometrioid tumors, since they have been shown to share similar prognosis [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, obesity in endometrial cancer survivors is also associated with poorer quality of life, particularly regarding physical and social functioning [ 46 , 47 ]. These obesity-based results are consistent with the adiposity result in the meta-analyses [ 40 , 41 ] in that it is clear that individuals who are morbidly obese carry massive amounts of adipose tissue. Interestingly, there is a more well-established relationship between BMI and cancer recurrence for breast cancer patients.…”
Section: Discussionsupporting
confidence: 84%
“…Specifically, meta-analyses have uncovered associations between BMI status at endometrial cancer diagnosis and cancer recurrence and all-cause mortality [ 39 ]. While BMI was not associated with cancer-specific mortality in this study, a relationship was observed between visceral fat and cancer-specific mortality in two of the studies included in the meta-analysis [ 40 , 41 ]. This is extraordinarily important because the effect of obesity is mediated nearly exclusively by adipose tissue.…”
Section: Discussioncontrasting
confidence: 62%
“…Currently, endometrial cancer patients are still more likely to die of cardiovascular disease than endometrial cancer [ 56 ]. Sustainable lifestyle changes could positively influence long-term survival and recurrence of cancer patients [ 57 , 58 ]. Therefore, it is clear that there is a need for future prospective randomised studies to assess the short-term and long-term impact of prehabilitation for gynaecological cancer patients.…”
Section: Discussionmentioning
confidence: 99%